Internet Revolutions, Democratic Globalization and Elections Outcome in the Twenty-First Century: Echoes from Nigeria (Glocalism: Journal of Culture, Politics and Innovation, 2017)
This paper examines the social contexts of the development and innovation of the science of global communication technology. It shows the significant roles the internet has played in the democratic process, and in particular, how it has influenced the outcomes of elections across developed and developing societies in an increasingly globalised community. This paper argues that Facebook, Twitter, WhatsApp, blogs and LinkedIn etc. serve as the mediums through which civil rights and democratic activism are expressed. It also argues that during the 2011 and 2015 General Elections in Nigeria, many electronic devices and online programs were developed and used on social media. Revoda enabled a parallel vote count, access to polling unit results, transmission of collated results and information about the entire electoral process. The paper stresses that the use of social media networks by both political candidates and electorates has greatly promoted civic engagement, credible elections and democratic activism in pre-election and post-election periods. This paper concludes that internet technology may soon assume the position of an effective and critically vital para-human actor in most global election outcomes in the near future.
Keywords: Internet revolutions; democratic globalisation; election outcomes; Nigeria